Report on the conclusions and recommendations (InterAction Council New YorkUS, 1994)
Looks at aspects such as multilateral organizations and the new global agenda; the maintenance of peace and global security; managing economic interdependence; and, managing the new global challenges viz. population explosion and sustainable development.
DC